Protecting HaCaT cells from ionizing radiation using persimmon tannin-Aloe gel composite - Xi Qian; Zhongmin Wang; Jinliang Ning; Chaoke Qin; Lin Gao; Na He; Dahong Lin; Zhide Zhou; Guiyin Li (Taylor & Francis Group, 2020)
Context Persimmon tannin (extract of Diospyros kaki L.f [Ebenaceae]) and Aloe gel (extract of Aloe vera (L.) Burm.f. [Asphodelaceae]) are known as anti-radiation agents. However, radiation resistance of the persimmon tannin-Aloe gel composite remains inconclusive. Objective To investigate the capacity of the persimmon tannin-Aloe gel composite to protect against ionising radiation at the cellular level. Materials and methods HaCaT (human epidermal keratinocytes) cells were pre-treated with PT-A-1 (the mass ratio of persimmon tannin and Aloe gel was 2:1) or the single component (persimmon tannin or Aloe gel) at various concentrations (0, 50, 100, 200, 400, 800 μg/mL. Control group: medium with no HaCaT cells), and then radiated with X-rays (radiation dose: 4, 8, 12, 16, and 20 Gy). Cell viability, cell apoptosis, and radiation-induced intracellular reactive oxygen species (ROS) generation were analysed by CCK-8, Hoechst 33258 staining/flow cytometry, and 2',7'-dichlorfluorescein diacetate (DCFH-DA) assay, respectively, for 12 or 24 h incubation after radiation. Results The optimal radiation dose and post-radiation incubation period were determined to be 8 Gy and 12 h. CCK-8 activity detection showed that the cell activity was 77.85% (p < 0.05, IC50 = 55.67 μg/mL). The apoptotic rate was the lowest (4.32%) at 200 μg/mL of PT-A-1 towards HaCaT cells. ROS production was the most effectively suppressed by 200 μg/mL PT-A-1 towards HaCaT cells. Discussion and conclusions The persimmon tannin-Aloe gel composite has good radioprotective effect, and which will facilitate its clinic application as a potential natural anti-radiation agent in future.